Impact of Zn-doped Manganese Oxide Nanoparticles on Structural and Optical Properties - Yadav, V.; Shukla, R.; Sharma, K. S. (Journal of Scientific Research, 2022)
In the present work, the structural and optical properties of pure and zinc-doped manganese oxide nanoparticles prepared by the sol-gel method have been studied for doping concentrations of 5, 10, and 15 %. The XRD patterns reveal that the cubic phase of pure manganese oxide nanoparticles is changed to tetragonal on doping with Zn. The surface morphology of pure and Zn doped manganese oxide nanoparticles has been studied by Scanning Electron Microscopy (SEM), which reveals appreciable changes in size and shape of the nanoparticles as the doping level of Zn is increased. The optical properties studied by UV-Visible spectroscopy further reveal that the energy band gap increases with a decrease in the size of nanoparticles.